Jimi Hendrixin ”Star-Spangled Banner”: näkökulmia Woodstock-festivaalin (1969) aikalaiskontekstiin ja kulttuuriperintöön - Mähkä Rami (Finland, 2025)
Using Jimi Hendrix's avantgardist interpretation of the US national anthem as a prism, the article discusses the contemporary contexts and later heritage of the Woodstock festival (1969).